2014
DOI: 10.1590/0100-2945-368/13
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética, crescimento e produção de genótipos de bananeira 'Prata-Anã' em área com mal do panamá

Abstract: resumo -No perímetro irrigado do Jaíba, no norte de Minas Gerais, existem relatos sobre a presença de alguns genótipos de banana'Prata-Anã' supostamente tolerantes ao mal-do-panamá, nos quais a doença não se estabeleceu após 15 anos de cultivo, mesmo na presença do patógeno. Portanto, objetivou-se avaliar a diversidade genética, o desempenho agronômico e o comportamento dos clones da bananeira'PrataAnã' cultivada em área com histórico do mal-do-panamá. Foram coletados vinte e quatro genótipos, 11 caracterizado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The variation coefficients values oscillated with the evaluated characteristic and with the production cycle (Figures 3 and 4), similarly to Ortiz (1995) and Lopes et al (2014) as expected, since the first cycle is less subject to environmental and management conditions compared to the following cycle.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The variation coefficients values oscillated with the evaluated characteristic and with the production cycle (Figures 3 and 4), similarly to Ortiz (1995) and Lopes et al (2014) as expected, since the first cycle is less subject to environmental and management conditions compared to the following cycle.…”
Section: Resultssupporting
confidence: 75%
“…In autogamous crops, and more markedly, in asexual propagation plants such as banana, genetic variability is minimal, although somaclonal variation at high level may occur (LOPES et al, 2014), probably due to mitotic instability and / or mutation (GUAPACHA et al, 2017), which are not exclusive to tissue culture, but also observed in the field, but at lower frequencies. In this work, index b is a consequence of soil anisotropy and other factors affecting the degree of experimental heterogeneity, such as errors from planting techniques, cultural practices, harvesting and measurements, as well as interferences and variations of climatic factors.…”
Section: Resultsmentioning
confidence: 99%
“…In each ISSR reaction, the total number of amplified fragments ranged from three (UBC-810 and UBC-864) to eight (UBC-817 and UBC-826), with a mean number of six bands per primer (Table 2 and Figure 1). Lower levels of polymorphism (33 and 34%) were found in banana Prata-Anã genotypes by Lopes et al (2014) and Rodrigues et al (2012), respectively, using RAPD molecular markers. In a study on Musa ssp cultivars, Ying et al (2011) identified a high percentage of polymorphism (85.1%) using ISSR markers.…”
Section: Resultsmentioning
confidence: 84%
“…Frequently FOC persists in cultivated areas for years due to it is survival phase when it then interacts as saprophytic in cultural remains or produces resting spores known as chlamydospores besides surviving and multiplying in alternative hosts [ 30 , 35 , 36 ]. The disease is characterized by yellowing of the young leaves, and pseudostem splitting, and eventually death of the plant [ 30 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%